2015
DOI: 10.1590/0103-8478cr20141538
|View full text |Cite
|
Sign up to set email alerts
|

Physical characteristics of potato flour from 'Ibituaçú' cv. under different extrusion parameters

Abstract: O IE dos produtos variou de 3,22 a 5,47, o VE de 2,08 e 11, o ISA de 32,88 a 63,72%, o IAA de 4,02 a 8, D de 7,54 a 29,85kgf, L* de 53,89 a 68,72, a* de 5,59 a 6,92, b* de 16,6 a 22,6. Nas condições de elevada temperatura, baixa umidade, e rotação da rosca intermediária são obtidos produtos extrusados com características físicas desejadas para produtos expandidos. Palavra-chave: Solanum tuberosum L., extrusão, propriedades físicas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
3
2
0
Order By: Relevance
“…Indeed, during the skinning, it could be that the germ storage place of the starch was affected, which also affected the starch content of this flour. The starch content is similar to that showed by Cardoso, Garcia, Do Carmo, Mischan, and Magali () who have obtained 62.23% as potato ( Ibituaçu ) flour starch contents. The reducing sugar content varies from 0.65% to 0.21%.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Indeed, during the skinning, it could be that the germ storage place of the starch was affected, which also affected the starch content of this flour. The starch content is similar to that showed by Cardoso, Garcia, Do Carmo, Mischan, and Magali () who have obtained 62.23% as potato ( Ibituaçu ) flour starch contents. The reducing sugar content varies from 0.65% to 0.21%.…”
Section: Resultssupporting
confidence: 89%
“…The decrease in amylose content in roasted and dehulled might have due to more destruction of α‐1.4 glycosidic bonds during these treatments. The reducing sugar are the same to that obtained by Cardoso et al (), who was 0.40%. Their value is affected by treatment and this confirm the purpose say before.…”
Section: Resultssupporting
confidence: 89%
“…Aguilar- Palazuelos et al (2012) reported that probably due to the addition of soy flour in the mix, the EI of snacks with potato starch and corn flour decreased. Furthermore,Cardoso et al (2015) found similar values of EI, to that reported byAguilar-Palazuelos et al (2012), and obtained higher values under conditions of lower moisture content and higher extrusion temperature of potato flour Soison et al (2014). observed that the moisture content had a greater effect on the EI, since when the moisture increases, the expansion of extrudates made from sweet potato flour decreases.…”
supporting
confidence: 81%
“…It is also the indicator of the behavior of the extrudate during its interaction with water in subsequent processing and the degree of starch conversion (Dalbhagat et al, 2019), while the WSI measures the amount of soluble components released after extrusion; in addition, high WSI is an indicator of excellent starch digestibility because it implies the degree of gelatinization and dextrinization (Dalbhagat et al, 2019; Yousf et al, 2017). Cardoso et al (2015) elaborated potato extrudates and found that, by using high temperature, low moisture, and intermediate screw speed, high WAI values can be obtained, while Peluola‐Adeyemi and Idowu (2014) found that the high moisture content and high screw speed increase the water absorption of the taro extrudate. However, it was observed that high temperature caused a reduction in WAI, WSI decreased with high moisture content, but increased with high temperature.…”
Section: Effect Of Use Of Tubers On the Physicochemical And Technofun...mentioning
confidence: 99%
See 1 more Smart Citation